Pengaruh Konsentrasi Doping terhadap Intensitas Emisi Material Luminisensi ZnO:Zn: Diky Anggoro, Rizki Yuniasari, Hasto Sunarno, F Faridawati - Diky Anggoro Diky Anggoro; Rizki Yuniasari Rizki Yuniasari; Hasto Sunarno Hasto Sunarno; Faridawati Faridawati (Jurnal Fisika dan Aplikasinya, 2018)
The luminance of Zinc Oxide materials has been synthesized using the phase solution method. The calcination process is carried out at a temperature of 8000 C. Performed phase identification, optical characterization, and luminance intensity generated by ZnO synthesis results. Addition of doping was done by using doping concentration of 1%, 3%, and 5% with a calcination temperature of 3000 C to obtain ZnO: Zn. We do phase identification and optical characterization of the three samples produced. The intensity of luminescence was tested to determine the effect of adding doping concentrations to the emissions produced by luminance materials ZnO: Zn. Obtained luminance material results emit green emissions with 510 nm to 535 nm wavelength range. The higher the doping concentration will be the more activators (doping) in the host (ZnO) that absorbs the energy for the excitation process so that the higher emission intensity emitted.